KEMAMPUAN BERPIKIR KRITIS SISWA DALAM PENYELESAIAN SOAL MATERI PERTIDAKSAMAAN LINEAR SATU VARIABEL DI SMP - Idawati Munte, Desirapma; Yusmin, Edy; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract Critical thinking abilities is necessary to deliver more leads through thinking and working process in solving problems so that more accurate in determining the relevance of things. The common purpose in this research is to describe students’ critical thinking abilities in solving the problem on material learning of linear inequalities in one variable at the VII grade of SMP Negeri 3 Pontianak. The form of this research is descriptive qualitative. The subjects in this research are students who have been obtained learning material of linear inequalities in one variable. The technique of data collection are assesment technique and interview technique . In general, the results of the research are the student’s ability to interpret mostly belong to good category , the student’s ability to analyze mostly belong to very deficient category, and the student’s ability to evaluate mostly belong to very deficient category. Keywords: Critical thinking, ability to interpret, ability to analyze, ability to evaluate, linear inequalities in one variable